THE FIRST FIND OF A CRETACEOUS RELIC BATTARREA PHALLOIDES (DICKS.) PERS. IN FOREST COMMUNITIES IN THE LOWER REACHES OF THE URAL RIVER VALLEY (Experimental biology, 2021)
This article reports on the first find of a relic of the Cretaceous period on the territory of the West Kazakhstan region, where today the mycobiota has been little studied. As a result of studying the species composition of macromycetes in the forest communities of the Ural River valley, a new habitat of the Cretaceous relic was discovered, a unique species common in arid regions around the world, also on sands in a temperate climate Battarrea phalloides (Dicks.) Pers. Distribution area of Battarrea phalloides (Dicks.) Pers. occupies the steppe and desert zones of Eurasia. In the Republic of Kazakhstan, the area of Battarrea phalloides (Dicks.) Pers. includes the eastern and southern regions, and there were also finds along the river. Ili, Chu, Charyn, Syrdaria, in the lower reaches of the Ittas river.